Ladies' pages : African American women's magazines and the culture that made them - Rooks, Noliwe, 1963- (Black women writers series., 2004)
Beginning in the late nineteenth century, mainstream magazines established ideal images of white female culture, while comparable African American periodicals were cast among the shadows. Noliwe M. Rooks & amp;rsquo;s Ladies & amp;rsquo; Pages sheds light on the most influential African American women & amp;rsquo;s magazines & amp;ndash; & amp;ndash;Ringwood & amp;rsquo;s Afro-American Journal of Fashion, Half-Century Magazine for the Colored Homemaker, Tan Confessions, Essence, and O, the Oprah Magazine & amp;ndash; & amp;ndash;and their little-known success in shaping the lives of black women. Ladies & amp;rsquo; Pages demonstrates how thes.